2016
DOI: 10.1371/journal.pone.0158651
|View full text |Cite
|
Sign up to set email alerts
|

MLVA Typing of Streptococcus pneumoniae Isolates with Emphasis on Serotypes 14, 9N and 9V: Comparison of Previously Described Panels and Proposal of a Novel 7 VNTR Loci-Based Simplified Scheme

Abstract: Streptococcus pneumoniae remains as an important cause of community-acquired bacterial infections, and the nasopharynx of asymptomatic carriers is the major reservoir of this microorganism. Pneumococcal strains of serotype 14 and serogroup 9 are among the most frequently isolated from both asymptomatic carriers and patients with invasive disease living in Brazil. Internationally disseminated clones belonging to such serotypes have been associated with the emergence and spread of antimicrobial resistance in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The opaque phenotype was the most common overall and also within each one of all the clones investigated in this study, except for ST199 isolates, which we have shown to be a probable result of capsular switching events ( Costa et al, 2016 ). Among these three serotype 14 ST199 variants, two were exclusively composed of transparent variants, while the third was composed of a mixed phenotype, indicating that the genotype in which capsular recombination events were assumed to occur was also the only genotype where the transparent phenotype was more frequent.…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…The opaque phenotype was the most common overall and also within each one of all the clones investigated in this study, except for ST199 isolates, which we have shown to be a probable result of capsular switching events ( Costa et al, 2016 ). Among these three serotype 14 ST199 variants, two were exclusively composed of transparent variants, while the third was composed of a mixed phenotype, indicating that the genotype in which capsular recombination events were assumed to occur was also the only genotype where the transparent phenotype was more frequent.…”
Section: Resultsmentioning
confidence: 65%
“…However, ST199 isolates usually belong to serogroups 15 or 19 2 , and the ones included in the present study were of serotype 14, representing the first serotype 14 variants of this clone to be reported ( Pinto et al, 2016 ). We have also previously shown that these serotype 14 ST199 variants might have been generated by capsular switching events since they were genetically more closely related to strains belonging to serotype 15B than to other isolates of serotype 14 ( Costa et al, 2016 ). Previous studies have indicated that capsular switching events in pneumococci can lead to other simultaneous recombination events spanning a genome region of approximately 750 kb, which includes the capsular locus and the pilus type 1 operon ( Sjöström et al, 2007 ; Croucher et al, 2014 ; Metcalf et al, 2016 ); thus, in these serotype 14 ST199 variants, PI-1 coding genes could have been lost during recombination events in the capsular locus that led to serotype switching.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations